ARTIFICIAL INTELLIGENCE – THE POWER SOURCE OF THE FUTURE (Web of Teachers: Inderscience Research, 2026)
Throughout human history, progress and innovation have always propelled societies forward, but in the modern era, artificial intelligence technologies have become the main driving force behind this evolution. Artificial intelligence, often abbreviated AI, can be understood as the emulation of human cognitive abilities by machines and computer systems, allowing them to process information, make decisions, analyze problems, and learn from data through the use of specialized software and algorithms. What began as an idea in science fiction has become an integral part of daily life and global development.